Factors predicting the adhesion and prolonged lost days of work in patients with extensor tendon adhesion of the hand - Xiao, Gong; Wang, Jinzhong; Zhang, Ningjie; Hao, Juanjuan (Frontiers in Surgery, 2024)
We performed a retrospective study in patients with extensor tendon injuries who underwent primary surgical repair and early rehabilitation. We observed the differences between non-tendon adhesion and adhesion patients after surgical repair, and used the receiver operating characteristic curve to distinguish them. Then we explored the influencing factors of adhesion. In addition, we studied the lost days of work and the influencing factors.Results: A total of 305 patients were included. 24.6% patients appeared tendon adhesion and the mean lost days of work was 12 weeks. MHISS scores, VAS scores, occupation and blood triglyceride level were the influencing factors of adhesion. The adhesion patients have increased MHISS scores(p<0.001), VAS scores(p<0.001), blood triglyceride levels(p<0.001) and lost days of work(p<0.001) than non-tendon adhesion. The optimal cut-off value of blood triglyceride level to distinguish non-tendon adhesion from adhesion was 1.625mml/L, and MHISS scores was 20.5. Smoking, MHISS scores, blood triglyceride levels were the influencing factors of lost days of work in adhesion patients. There was positive correlation between lost days of work and triglyceride level (r=0.307, p=0.007), and MHISS scores (r=0.276, p=0.016).To minimize the occurrence of adhesion, doctors should pay attention to patients with higher MHISS and VAS scores, blood triglyceride levels, especial for the blue-collar and unemployed one. High triglyceride level may be a new influencing factor. Keywords: extensor tendon repair; hand; tendon adhesion; prolonged lost days of work; Triglyceride level;The tendon injury represents the second most common injury of the hand (after fractures) (Yoon and Chung,2019). The extensor tendon injury accounts for 20% of the whole flexor and extensor tendon injury of the hand. Extensor tendons are susceptible to damage because of their relatively thin and soft tissue coverage (Yoon and Chung,2019). Early treatment of extensor tendon injury is essential to clinical outcome(Snow